Raman and X‐ray Studies of Uranium–Lanthanum‐Mixed Oxides Before and After Air Oxidation. Issue 7 (26th March 2015) - Talip, Zeynep; Wiss, Thierry; Raison, Philippe E.; Paillier, Jérôme; Manara, Dario; Somers, Joseph; Konings, Rudy J.M.; Besmann, T.
<x xml:space="preserve">Abstract</x> UO2 samples doped with 6, 11, 22 mol% lanthanum were examined before and after air oxidation. To verify the formation of uranium–lanthanum‐mixed oxide solid solutions, powder X‐ray diffraction (XRD) analyses of the crystalline phases in the materials were carried out. The presence of oxygen vacancies in the La‐doped UO2 samples was identified by Raman spectrometry. It was evidenced by changes induced in the Raman spectra by air oxidation. This latter was carried out either by increasing the Raman laser power or by thermally treating the samples at 500 K for 370 h. In addition, oxidation behavior differences of pure and La‐doped UO2 samples were reported by comparing XRD and Raman results of the samples before and after air oxidation. It was shown that the concentration of the M4O9 (M: U, La) phase increased with increasing content of La, whereas inhibition for the formation of M3O8 phase was observed.